Analysis of heavy metals content in well water and its predictive insights for students' wellbeing in Almajiri Schools, Sokoto East, Nigeria - Sarkingobir, Yusuf; Umar, A.I.; Waheed, Syed A.; Miya, Yusuf Yahaya; Sahabi, Mustapha; Salah, Nura Maiakwai (International Journal of Research in STEM Education, 2023)
Education is a right to every child, but Sokoto is suffering from many issues ravaging education, therewith, a major issue is the Almajiri school. Because the Almajiri schools are abandoned there is every tendency that their drinking water is contaminated considering the rising pattern of pollution across the globe. The aim of the study was to carry out an analysis of heavy metal content in well water and propel some predictive insights for students well-being in Almajiri schools in Sokoto, Nigeria.  Samples of well water were collected from Almajiri schools in Sokoto state and metals were analyzed using atomic abortion spectroscopy. 60.10 ± 5.1 to 600.1± 0.01, 100.1 ± 0.5 to 600.0 ± 0.02, are the ranges of calcium, and magnesium macroelements determined.  The ranges for essential heavy metals zinc, and iron are as follows; 2.34 ± 0.05 to 5.00 ± 0.02 (zinc), and 0.54± 0.05 to 10.43 ± 0.5 (iron) respectively. The ranges of Pb, Hg, and Cd assessed are as follows: lead (0.0 to 1.06 ± 0.005), mercury (0.10 ± 0.002 to 2.501 ± 0.01), and cadmium (0.00122 ±0.0004 to 0.0761 ± 0.0001). The HI for the heavy metals determined are in the order of schools B>D>A>C. The metals determined are either excess or little (with respect to essential heavy metals) in many cases.  In one school, the HI is far above 1 and therefore risk the population with effects. Thus, can elicit harm to the consumers. They can affect the academic, cognitive capacity of the Alamjiri children. There is need to take proper measures to save the health and future development of the Almajiri child against heavy metals poisoning possibility.